Relationships between molds and asthma suggesting non‐allergic mechanisms. A rural‐urban comparison. Issue 4 (21st May 2013) - Flamant‐Hulin, Marion; Annesi‐Maesano, Isabella; Caillaud, Denis
Abstract Background A fungal index, based on specific microbial volatile organic compounds (MVOCs) emission, was employed and related to asthma in children from rural and urban dwellings after stratification on the children atopic status. Methods A nested case‐control design was used to draw, from 2 cross‐sectional surveys, 20 asthmatics and 26 controls living in urban areas, and 24 asthmatics and 25 controls in rural areas. MVOCs levels were assessed in the living‐room during one week; during that week, children performed clinical tests and their parents were invited to fill in a questionnaire on respiratory health. Results According to the objective fungal index, 70.5% of cases and 49.0% of controls were exposed to molds. More children with current asthma had experienced mold exposure in their homes (OR=3.38, 95% CI (1.16; 9.90)), especially amongst children living in rural areas. Atopic status modified this association: exposure to molds was found to be related to current asthma only in non‐atopic children (OR=10.42, 95% CI (2.42; 44.81)). Among urban ‐dwelling children that could be screened at hospital, asthmatic children living in contaminated dwellings had a higher proportion of blood neutrophils and a lower FEV1 (forced expiratory volume in 1 second) than non‐exposed ones. Conclusion Our findings based on an objective assessment of MVOCs suggest adverse respiratory effects of molds. Our results suggest that when looking at the aetiology of non‐atopic asthma, mold exposure should be systematically assessed.